Development of Experimental Research on Heat Transfer and Friction Characteristics of Fin-and-tube Hechanger-correlation - 刘建; 魏文建; 丁国良; 张春路 (Zhileng xuebao)
This paper summaries the heat transfer and pressure drop correlations of different fin surfaces, and the corresponding influencing factors. The evaluation criteria of enhanced surface performances have also been described. The appropriate correlation and evaluation criterion will provide reliable foundation to the design and optimization of compact heat exchangers.